Lymphocyte / monocyte index as pronostic factor in diffuse large b cell lymphoma, Edgardo Rebagliati Martins hospital 2010-2017: Índice linfocito/monocito como factor pronóstico en linfoma células grandes b difuso, hospital Edgardo Rebagliati Martins 2010-2017 - Beltrán, Brady (2019)
Introduction: The lymphocyte / monocyte index (ILM) has been described as an inflamatory prognostic parameter in many hematological diseases and solid tumors. The aim of the present study was to evaluate the prognostic value of the lymphocyte / monocyte index in the survival of patients with diffuse large B-cell lymphoma (LCGBD). Methods: The present is an analytical, longitudinal and non-experimental study. Patients diagnosed with diffuse large B-cell lymphoma of the Edgardo Rebagliati Martins hospital from 2010 to 2017 were selected. Results: 121 patients were included, 57% female, 66.1% older than 60 years. Regarding the Performance Status Zubrod, 66.5% corresponded to the degree of best forecast 0 and 1; 59.5% presented associated B symptoms. Nearly 60% were stages I and II and 57% presented extranodal involvement. We show that the ILM is significant for overall survival in the regression analysis of bivariate cox, not reaching significance in the multivariate. Conclusion: ILM is a potential simple and accessible prognostic biomarker for our population with diffuse large B-cell lymphoma. DOI:10.25176/RFMH.v19.n2.2068